Is it safe to perform total arterial grafting in elderly patients lacking vein grafts? A single surgeon comparison. Issue 12 (8th October 2022) - Acharya, Metesh; Khan, Habib; Chaubey, Sanjay; Mittal, Aaina; Hussain, Azhar; Wendler, Olaf
Abstract: Objectives: The results of coronary artery bypass graft (CABG) surgery with total arterial revascularisation (TA‐CABG) in elderly patients, who may have insufficient vein graft material for conventional CABG (CO‐CABG), have not been fully established. We therefore sought to compare the short‐ and long‐term outcomes of patients >70 years old undergoing CO‐CABG and TA‐CABG. Methods: We performed a retrospective observational study analyzing all consecutive adult patients aged >70 years undergoing first‐time CABG over the 15‐year period from 2004 to 2020 under a single surgeon. Primary outcomes of interest were in‐hospital mortality, long‐term mortality, and re‐intervention rate. Secondary outcomes of interest included operative durations and the incidence of peri‐operative complications. Results: There were 46 patients (age 76 ± 3 SD) in the TA‐CABG group and 145 patients (age 76 ± 4 SD) in the CO‐CABG group. Cardio‐pulmonary bypass and cross‐clamp durations were comparable between groups ( p = .11 and p = .23, respectively). Stroke occurred in 1.0% undergoing CO‐CABG compared to 0% in the TA‐CABG group ( p = .42). Hospital mortality was 3.0% with CO‐CABG (EuroSCORE; mean [SD] 6.81 (5.81)) and 2.0% with TA‐CABG (EuroSCORE; mean [SD] 6.38 (6.57)) ( p = .93). On long‐term follow‐up, myocardial infarction occurred in 10.0% of CO‐CABG patients compared to 4.0% of TA‐CABG patients ( p = .25). Re‐intervention rates were 7% following CO‐CABG, and 2% after TA‐CABG ( p = .23). There was no significant difference in long‐term mortality between patients undergoing CO‐CABG and TA‐CABG (47% vs. 57%, p = .27). Long‐term survival was comparable between grafting techniques ( p = .27). Conclusions: There were no significant differences in major adverse cardiac and cerebrovascular events, re‐intervention rate, hospital or long‐term mortality between CO‐CABG and TA‐CABG. TA‐CABG represents a safe and feasible alternative to CO‐CABG in elderly patients offering good long‐term outcomes.